If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6j=-4-10j
We move all terms to the left:
-6j-(-4-10j)=0
We add all the numbers together, and all the variables
-6j-(-10j-4)=0
We get rid of parentheses
-6j+10j+4=0
We add all the numbers together, and all the variables
4j+4=0
We move all terms containing j to the left, all other terms to the right
4j=-4
j=-4/4
j=-1
| 2(4-4x)=7x+14-2x | | s+16.5=19 | | 7f-4-2=6f+2 | | -3(-5-3x)=87 | | 8w=-10+9w | | x+10°+3x+2°+4x-24°+2x+2°=360° | | h+28=12 | | 2c-2=4c+8 | | 7+2h=3h | | X-0.8x=174 | | 8(6+8x)=-336 | | 16v=54+7v | | -15+6n-n=6n-8 | | n/9=25/n | | -7(-3x-1)=91 | | 3/4.b=-15 | | r+8=44 | | 7u−10=5u+8 | | 90=-5(4x-6) | | -4n=-3-3n | | 4x+2(x+2)=3(2x+4) | | 2{4p+1}=10 | | -8-2v=-v | | 6x-5(x+5)=5x-6(x-4) | | 9-5w=-3w-9 | | 0^2=x+4 | | 4{x+1}-7=6x-2{4+x} | | b+1/6=-1 | | 45/3x+25=28 | | 14-4(x-3)=2(2x+8)-5 | | 0=m/9+1 | | x/2-3x-3/2=x/2+9/2+4 |